Programmed Cell Death: Complex Regulatory Networks in Cardiovascular Disease - Zhou, Liuhua; Sun, Jiateng; Gu, Lingfeng; Wang, Sibo; Yang, Tongtong; Wei, Tianwen; Shan, Tiankai; Wang, Hao; Wang, Liansheng (Frontiers in Cell and Developmental Biology, 2021)
Abnormalities in programmed cell death (PCD) signaling cascades can be observed in the development and progression of various cardiovascular diseases, such as apoptosis, necrosis, pyroptosis, ferroptosis, and cell death associated with autophagy. Aberrant activation of PCD pathways is a common feature leading to excessive cardiac remodeling and heart failure, involved in the pathogenesis of various cardiovascular diseases. Conversely, timely activation of PCD remodels cardiac structure and function after injury in a spatially or temporally restricted manner and corrects cardiac development similarly. As many cardiovascular diseases exhibit abnormalities in PCD pathways, drugs that can inhibit or modulate PCD may be critical in future therapeutic strategies. In this review, we briefly describe the process of various types of PCD and their roles in the occurrence and development of cardiovascular diseases. We also discuss the interplay between different cell death signaling cascades and summarize pharmaceutical agents targeting key players in cell death signaling pathways that have progressed to clinical trials. Ultimately a better understanding of PCD involved in cardiovascular diseases may lead to new avenues for therapy.